Secondary Level Students’ Experiences of Cyberbullying through Facebook - Dahal, Betendra Kumar (Journal of NELTA Gandaki, 2023)
ICT users face various challenges due to the lack of knowledge and awareness to use its tools properly. Along with the spread of Facebook users, the trend of cyberbullying is gradually increasing among teenagers including school students who have been victimised daily. This study explores the students’ experiences of cyberbullying through Facebook and the strategies they apply to cope with cyberbullying. I employed the qualitative research method in which the semi-structured interview was designed to collect data from 16 participants. The finding of this study depicts that cyberbullying is experienced by the participants in various ways like sharing memes on Facebook wall and Messenger, using nicknames, using unacceptable (vulgar) words, teasing, threatening, hacking Facebook passwords, and using, proposing for being close friends and joining photos and uploading, sending messages time and again and calling during night time. The study also found that cyberbullying makes victimised people feel insecure. It was also suggested to report with the family members and friends making strict laws, keeping in school level curriculum and launching mass awareness to cope with the cyberbullying activities found in the school level students of Nepal.